Partnership Dalam Pengelolaan Sektor Pariwisata Kampung Leduwi Kota Semarang - Ayu Siti Wahyuningsih; Yuliana Rohmawati; Retno Sunu Astuti (Departemen Administrasi Publik, Universitas Diponegoro, 2020)
Contribution of creative industries on gross domestic products in 2018 reached Rp 1.105 trillion. Craft contributed 15.7% to national gross domestic products and became the second dominant subsector in Central Java. Leduwi village is determined to be a leather/imitation center in Decree Number 531/978 of 2017. The issuance of decree is expected to increase the number of tourist and impact on economic progress. Tourism can be used as a development tool to cultivate economic diversification, alleviate poverty and create a good relationship between stakeholders. Leduwi village failed to become a tourist destination because there is no partnership in the management of creative industry so the economic growth becomes slowly. This research method uses the study of the library. Partnerships require: (1) Two or more parties, both governments, private/business and community; (2) The similarity of vision in achieving a common goal (3) between government and private agreements in the management that further gives positive effect to the economy of the surrounding community; (4) Mutual need between stakeholders. Cooperation between private and government parties is required to develop tourism destinations of Leduwi village as well as community roles to play an active role in the planning and development of tourist destinations.